2018
DOI: 10.1021/acs.orglett.8b02038
|View full text |Cite
|
Sign up to set email alerts
|

Thioether-Directed Selective C4 C–H Alkenylation of Indoles under Rhodium Catalysis

Abstract: A thioether-directed Rh(III)-catalyzed C4 selective C-H alkenylation of indoles via the formation of 5-membered metallacycle intermediates is reported. This protocol allows a wide functional group compatibility and broad substrate scope. The directing group can be readily removed or transformed into other functional groups after the C-H functionalization event. The catalytic method is also applicable to related heterocyclic systems involving benzo[ b]thiophene and benzo[ b]furan scaffolds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 43 publications
0
21
0
1
Order By: Relevance
“… 10 Recently, Miura et al reported the use of thiomethyl ether as an efficient directing group for C4 C–H functionalization. 11 In another study, You described a pivaloyl group-assisted C2/C4 heteroarylation of indoles by a controlled metalation tuning. 12 However, in all the above cases stoichiometric quantities of reagents are required to remove the directing group, which significantly limits the utility of these approaches in a synthesis.…”
mentioning
confidence: 99%
“… 10 Recently, Miura et al reported the use of thiomethyl ether as an efficient directing group for C4 C–H functionalization. 11 In another study, You described a pivaloyl group-assisted C2/C4 heteroarylation of indoles by a controlled metalation tuning. 12 However, in all the above cases stoichiometric quantities of reagents are required to remove the directing group, which significantly limits the utility of these approaches in a synthesis.…”
mentioning
confidence: 99%
“…As a recent contribution in this field, we reported a rhodium‐catalyzed C4‐selective alkenylation using a thioether as a traceless directing group . Encouraged by this achievement, we turned our interest in developing a new catalytic system for the C4‐selective direct alkynylation, and found that the target reaction was feasible using an analogous iridium catalyst and the EBX reagent 2 (Scheme c).…”
Section: Methodsmentioning
confidence: 99%
“…A thioether‐directed C4‐selective Rh(III)‐catalyzed oxidative alkenylation is developed (Scheme 15). [18] The reaction occurs through a five‐membered rhodacycle. A wide range of alkenes, acrylate esters, acrylonitrile, vinyl phosphonate and styrenes, and electronically varied indoles are tolerated.…”
Section: Functionalization Of C(4)−h Bondmentioning
confidence: 99%